Faktor Lingkungan Laut yang Mempengaruhi Laju Transisi Tahun Kedua Rishiri Kombu di Pulau Rebun: Faktor lingkungan laut yang memengaruhi laju transisi tahun kedua Rishiri Kombu di Pulau Rebun - Kawai, Tadashi; Akino, Hideki (Department of Aquatic Resources Management, Faculty of Fisheries and Marine Science, IPB University, 2026)
The transition of Saccharina japonica var. ochotensis (Rishiri Kombu) from its first to second year of growth is crucial for commercial harvest. However, recent increases in seawater temperature and nutrient depletion are likely to influence this process. This study investigates the influence of autumn seawater temperature and nitrate concentrations on the second-year transition rate of Rishiri Kombu in northern Hokkaido. Field surveys were conducted from 2020 to 2024 at Ishikari and Rebun, where the population densities of first- and second-year individuals were quantified. Concurrently, in situ measurements of seawater temperature and nitrate concentrations were performed during autumn. The results indicate that higher seawater temperatures tend to be associated with lower second-year transition rates, whereas increased nitrate concentrations positively correlate with transition success. Statistical analyses suggest that nutrient availability has a stronger influence on transition rates than temperature changes. These findings suggest that nitrate depletion is a key limiting factor for the sustainability of Rishiri Kombu, highlighting the importance of monitoring climate-driven changes in nitrate availability in coastal ecosystems.